Polymorphism of mitochondria in rat auriclar contractive cardiomyocites under the chronic alcoholic intoxication - Dunaev A.V.; Mishalov V.D. (Морфологія, 2007)
A number of the questions related to the reactions of mitochondrial apparatus of atrial cardiomyocites under the chronic alcoholization were dissolved in this study. The purpose of the study was to analyze morphological reactions of mi-tochondrial apparatus of atrial contractive cardiomyocites in rats on the chronic alcoholic poisoning. Modeling of the chronic alcoholic poisoning in rats was realized by daily introduction of ethyl alcohol per os in dosage 2-3,5 mg/g of rat weight dur-ing 30 days. Morphological research comprised both light and electronic microscopy of myocardium of right and left atria, right and left auricles, and also interatrial septum. Stereological estimation of several indexes was carried out: the compact-ness of mitochondria, numeral compactness of mitohondria, surface area of external mitochondrial membrane, compactness of mitochondrial cristae, number of mitochondrial cristae, surface area of internal mitochondrial membrane, degree of cristae orientation, coefficient of mitochondrial sphericity, volume of mitochondrium, quantitative correlation of types of mitochon-dria. It was shown that the reaction of different types of mitochondria on development of chronic alcoholization in atrial con-tractive cardiomyocites depends on the structural-metabolic type of mitochondria. Under the chronic alcoholic poisoning the moderate diffuse reduction of mitochondrial apparatus of contractive cardiomyocites takes place that is accompanied by the prolonged renewal of high-energy mitochondria and causes energetical limitation of contractive function of atrial myocar-dium.